The relationship between academic motivation and moral sensitivity in nursing students - Parisa Nezhadhoseini; Seyed Kazem Mousavi; Ali Javadzadeh (BMC Medical Education)
Abstract Background A Bachelor’s degree in nursing is one of the most challenging programs in the field of medical sciences. As a result, maintaining students’ academic motivation at the desired level is a constant concern for policymakers and educational administrators. Furthermore, tackling complex ethical dilemmas is inherent in nursing, making the educational period an important moment to instill moral sensitivity and reinforce professional ethics in students. This study aimed to investigate the association between academic motivation and moral sensitivity among undergraduate nursing students. Methods In this descriptive-correlational study, 265 undergraduate nursing students from the Abhar School of Nursing at Zanjan University of Medical Sciences in Iran were chosen using a census approach in 2024. The data collection tools included demographic surveys, the Academic Motivation Scale (AMS), and the Moral Sensitivity Questionnaire (MSQ), all completed online. The data were analyzed with SPSS version 16 software, which used descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (independent t-test, ANOVA, Pearson correlation, and multiple regression) with a significance level of 0.05. Results Nursing students had average academic motivation and moral sensitivity ratings of 79.24 ± 14.05 and 121.12 ± 16.33, respectively. Furthermore, a significant relationship was found between the overall scores and all dimensions of academic motivation and moral sensitivity (p < 0.001). Additionally, 29.1% of the variance in moral sensitivity was explained by the dimensions of the student’s academic motivation. Conclusion This study’s findings revealed a link between academic motivation and moral sensitivity among nursing students. As a result, it is advised that levels of academic motivation be continually checked during the program. This will assist in identifying students at danger of losing motivation and allow for the development and execution of effective initiatives to improve their academic engagement.